2018
DOI: 10.3390/antiox7070083
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Oxidative Stress and Platelet Activation in Coronary Thrombus of STEMI Patients

Abstract: Background: Platelet activation and oxidative stress seem to play a key role in coronary thrombus formation and are associated with thrombus burden in ST-elevation myocardial infarction (STEMI). However, the interplay between oxidative stress and platelet activation has not been fully elucidated. Materials and Methods: For 32 patients with STEMI undergoing primary percutaneous coronary intervention (PPCI) and 10 patients with stable angina (SA) and oxidative stress, as assessed by NADPH isoform 2 activity (sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Therefore, HDL has an anti-inflammatory effect and antioxidant properties that may prevent the oxidation of low-density lipoprotein (LDL). Oxidized LDL (oxLDL) increases the risk of both endothelial dysfunction and changes in vessels owing to infiltration by leukocytes and induction of inflammation [8,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, HDL has an anti-inflammatory effect and antioxidant properties that may prevent the oxidation of low-density lipoprotein (LDL). Oxidized LDL (oxLDL) increases the risk of both endothelial dysfunction and changes in vessels owing to infiltration by leukocytes and induction of inflammation [8,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…These events increase the risk of cardiac microvascular occlusion and myocardial dysfunction, a contention that is supported by findings that various biomarkers of platelet activation and neutrophil:platelet aggregates, as well as NETs and their constituents, such as histones, are major components of intravascular thrombi (134)(135)(136). In this context it is noteworthy that systemic histones, presumably derived from NETs, are associated with thrombocytopenia in critically ill patients, an association that has also been observed following experimental administration of histones to mice (137,138).…”
Section: Evidence Linking Platelet Activation To the Pathogenesis Of mentioning
confidence: 90%
“…32 Calvieri et al recently showed a correlation between platelet activation and increased oxidative stress in patients with STEMI. 33 Reactive oxygen species damage is also the main mechanism in CIN pathogenesis. 34 Increased ROS products, as a result of toxic effects of contrast agents and hypoxia, are considered to be one of the major factors in CIN development.…”
Section: Discussionmentioning
confidence: 99%